(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper intends to comprehend the contemporary scenario of dairy farming and various concerned issues and problems that help in dampening the spirit and zeal of the farmers to take it up as their profession and mode of earning their livelihood in the rugged and mountainous terrain of Himachal Pradesh. In mountainous state of Himachal Pradesh the various issues of farmers who are involved in rearing cattle require redressal in order to promote dairy farming in the state. The farmers face number of problems like scarcity of high yielding milch cattle, shortage of feed and green fodder, inactive veterinary and diagnostic services, and lack of scientific understanding. The diligence of the people and the institutional efforts are required to raise the economic status and social identification of the people in the state. Agriculture is the main occupation and livestock is given special attention to supplement people’s income and fulfil their dietary requirements. Though peasants put more labour in their farms to get fodder to cattle, they don’t get remuneration in proportion to their toil because of domestic breed of milch cattle. Albeit the yield of the cattle is very low, people’s enthusiasm to rear cattle does not wither. They consider cattle as a social status and member of their families. In spite of such a healthy environment for dairy farming, they don’t perform it on commercial basis rather confine it only for subsistence level. The lacklustre efforts of the government seem to be the critical reason to restrict dairy farming to subsistence level in the state. The provision of high yielding milch cattle to the farmers is required for rapid promotion of dairy farming. Therefore, government and farmers are needed to work together for its swift promotion in the state.